2016
DOI: 10.1177/1591019916637344
|View full text |Cite
|
Sign up to set email alerts
|

Carotid siphon morphology: Is it associated with posterior communicating aneurysms?

Abstract: Background and purpose Posterior communicating artery (PComA) aneurysm seems to behave uniquely compared with other intracranial aneurysms at different locations. The association between the morphology of the carotid siphon and PComA aneurysms is not well known. This study aimed to investigate whether the anatomical characteristics of the carotid siphon are associated with the formation and rupture of PComA aneurysms. Methods<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…20 In addition, whether the geometry of the carotid siphon could led to aneurysm development is unclear. 16,18,22 Our results yielded shorter and narrower mean diameters and lengths of the entire MCA compared with previous reports. We also found shorter diameters in the MCA in the aneurysm group at the three studied segments.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…20 In addition, whether the geometry of the carotid siphon could led to aneurysm development is unclear. 16,18,22 Our results yielded shorter and narrower mean diameters and lengths of the entire MCA compared with previous reports. We also found shorter diameters in the MCA in the aneurysm group at the three studied segments.…”
Section: Discussionsupporting
confidence: 45%
“…20 In addition, whether the geometry of the carotid siphon could led to aneurysm development is unclear. 16 18 22…”
Section: Discussionmentioning
confidence: 99%
“…Lauric et al. showed that the high bend curvature of the carotid siphon could induce destructive vessel wall remodeling and siphon aneurysm initiation [ 9 ]; however, one study found no association between the morphological characteristics of the carotid siphon and the occurrence of PCoA aneurysm [ 10 ]. Patients with S‑shaped siphons, which are more torturous than V‑shaped siphons, were found to be less prone to developing IAs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tortuosity of the ICA is hypothesized to be associated with IA formation. Unexpectedly, another study revealed no link between the morphological characteristics of carotid siphons and the incidence of PCoA aneurysm [ 10 ]. Double bend (S-shaped) siphons are more tortuous than V‑shaped siphons.…”
Section: Introductionmentioning
confidence: 99%
“…The morphologic variations of the supraclinoid carotid siphon of the ICA are very important. ICA-PcomA aneurysm of the low-lying and short ICA carries potential risks, such as no clipping space for proximal control and hidden aneurysm complex under the tent 25, 26, 27, 28. As many as 11.1%–15.5% of ICA-PcomA aneurysms require either anterior clinoidectomy or resection of the tent for clipping via standard craniotomy 25, 29.…”
Section: Discussionmentioning
confidence: 99%